Ergonomics: a study on physical ergonomics related to job performance at Petronas Chemicals MTBE Sdn. Bhd. Kuantan / Shahirah Sha'amry - Sha'amry, Shahirah (2013)
The research entitled "Ergonomics: A Study on Physical Ergonomics Related to Job Performance of Employees at Petronas Chemicals MTBE Sdn. Bhd.". The study had two objectives highlighted which are to investigate the relationship between physical ergonomics and employees' job performance at PETRONAS Chemicals MTBE Sdn. Bhd., Kuantan. The scope of the study was focused on employees at Petronas Chemicals MTBE Sdn. Bhd. who spent most of their time in the work station and 40 respondents were selected for the data collection process. The study consists of Chapter 1: Introduction, Chapter 2: Literature Review, Chapter 3: Methodology, Chapter 4: Results/Findings of Study and Chapter 5: Conclusion and Recommendation. Each of the sub-topics has been discussed extensively in each of chapter. The researcher used correlation research as the research design and the sampling technique used was the probability sampling that emphasized on the stratified random sampling technique. The researcher has analyzed the independent (physical ergonomics) and dependent (job performance). The data analysis techniques are frequency distribution and correlations testing. Reliability test also was conducted due to measure the reliability of the questionnaire. This study aims to identify about their daily usage of physical ergonomics in order to know the relationship with the level of job performance. From the findings, a recommendation has been made to the organization and also for future research purpose.